2004
DOI: 10.1007/s10735-004-2653-0
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Computational modelling of cell & tissue processes & function

Abstract: Computational modelling of whole biological systems from cells to organs is gaining momentum in cell biology and disease studies. This pathway is essential for the derivation of explanatory frameworks that will facilitate the development of a predictive capacity for estimating outcomes or risk associated with particular disease processes and therapeutic or stressful treatments. This article introduces a series of invited papers covering a hierarchy of issues and modelling problems, ranging from crucial concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Mathematical models provide the conceptual and mathematical formalism to integrate molecular, cellular and whole animal processes (Allen & McVeigh, 2004;Allen & Moore, 2004;Moore & Noble, 2004). Previous studies have shown that network complexity (as evaluated using network connectedness -connectance CV%-and node size) can be used as an indicator of homeostasis or health in cellular systems (Moore, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models provide the conceptual and mathematical formalism to integrate molecular, cellular and whole animal processes (Allen & McVeigh, 2004;Allen & Moore, 2004;Moore & Noble, 2004). Previous studies have shown that network complexity (as evaluated using network connectedness -connectance CV%-and node size) can be used as an indicator of homeostasis or health in cellular systems (Moore, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This argument can probably also be applied to the ''health" of biological assemblages and ecosystems. Effective diagnosis of chemical pollutant impacts and predictions of their consequences requires that we have a capability to model biological interactions (Moore, 2002;Moore and Noble, 2004;Moore et al, 2006;Noble et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This ranges from sub-microseconds for molecular-level interactions to days, months, and even years for the development of a disease in humans. The complexities represented are such that descriptive intuition often fails and the combinatorial problems to be addressed become serious challenges [55] .…”
Section: The Modelling Approaches Required ▼mentioning
confidence: 99%